1996
DOI: 10.1523/jneurosci.16-09-02901.1996
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of the p75 Nerve Growth Factor Receptor in Glia and Neurons of the Rat Dorsal Root Ganglia after Peripheral Nerve Transection

Abstract: Sympathetic nerve terminals on blood vessels within the dorsal root ganglia sprout after sciatic nerve lesions in the rat. The mechanism underlying this phenomenon is not clear, but might be predicted to involve nerve growth factor or its homologs because these factors are known to trigger collateral sprouting of undamaged sympathetic noradrenergic terminals. We have found that sciatic nerve lesions lead to a decreased expression of neuronal p75, the low-affinity receptor for the neurotrophins, but an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
124
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(143 citation statements)
references
References 52 publications
15
124
1
1
Order By: Relevance
“…1C,D). The percentages of p75NTR mRNA-positive neurons in the present study are much lower than those previously reported (50 -60%) (Zhou et al, 1996;Bergman et al, 1999). This discrepancy may be attributable to the differences in the criterion used to distinguish between positively and negatively labeled neurons.…”
Section: P75ntr But Not Trks Mrna Increases In Intact Drg Neurons Acontrasting
confidence: 99%
“…1C,D). The percentages of p75NTR mRNA-positive neurons in the present study are much lower than those previously reported (50 -60%) (Zhou et al, 1996;Bergman et al, 1999). This discrepancy may be attributable to the differences in the criterion used to distinguish between positively and negatively labeled neurons.…”
Section: P75ntr But Not Trks Mrna Increases In Intact Drg Neurons Acontrasting
confidence: 99%
“…The reduction in the response of neurons to these inhibitory cues after peripheral nerve injury could be attributable to a modification or downregulation in the receptors that comprise the Nogo receptor complex. Expression of p75 in DRG neurons is downregulated after peripheral injury (Krekoski et al, 1996;Zhou et al, 1996) modification of downstream signal transduction paths or other effectors that lead to growth cone collapse may also contribute (Lehmann et al, 1999;Dergham et al, 2002;Sivasankaran et al, 2004;Spencer and Filbin, 2004;Domeniconi et al, 2005;Koprivica et al, 2005). The conditioning effect contributes therefore, both to an enhancement of axonal growth and a diminished response to myelin inhibitory signals.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that after axotomy SGCs proliferated and expressed high levels of neurotrophins (NTs) and the low affinity NT receptor p75 [193]. Interestingly, this increase was localized in SGCs around sensory neurons that innervate the skin, but not those innervating the muscle [74].…”
Section: Plasticity Of Sgcsmentioning
confidence: 99%